2007
DOI: 10.1111/j.1349-7006.2007.00568.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of cyclooxygenase‐2 in the tumor site‐dependent production of parathyroid hormone‐related protein in colon 26 carcinoma

Abstract: It has been shown that in the mouse colon 26 tumor model, tumors grown in the subcutis (subcutis colon 26) caused early onset of cachectic syndromes, whereas those in the liver (liver colon 26) did not. Both interleukin (IL)-6 and parathyroid hormone-related protein (PTHrP) were involved in the development of cachectic syndromes in this tumor model. However, whether expression of PTHrP and IL-6 is differently regulated in the tumor microenvironment is unclear. In the present study, culturing the colon 26 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
2
10
1
Order By: Relevance
“…DHA is known to reduce COX-2 activity [12], and PTHrP production is known to be stimulated upon stimulation of COX-2 [8]. Therefore, to further elucidate the possible mode of action of DHA, we determined whether COX-2 was involved in the PTHrP reducing effects of DHA in Experiment E. This was done by measuring PGE-2 production upon incubation of C26 cells with DHA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…DHA is known to reduce COX-2 activity [12], and PTHrP production is known to be stimulated upon stimulation of COX-2 [8]. Therefore, to further elucidate the possible mode of action of DHA, we determined whether COX-2 was involved in the PTHrP reducing effects of DHA in Experiment E. This was done by measuring PGE-2 production upon incubation of C26 cells with DHA.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, our results showed that the nutritional combination of fish oil and leucine reduced PTHrP levels in the tumour. Elevation of PTHrP in malignancy is thought to be mediated by an increase in COX-2 activity [8]. Therefore, the strong positive correlations of Ca 2+ levels with PGE-2, a major COX-2-mediated inflammatory mediator, might suggest that PTHrP is also involved in the induction of hypercalcemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been shown that truncated APC can target β-catenin for destruction, but only in the absence of COX enzyme activity, providing a possible molecular explanation for the promising results of COX-2 inhibition in colorectal cancer (Eisinger et al 2007). In vitro, the COX-2 inhibitor NS-398 suppressed parathyroid-related peptide (PTHrP) production in colorectal cancer (Saito et al 2007). Anti-PTH immunotherapy has been described in some case reports, demonstrating biochemical control and clinical improvement as well as reduction of the size of metastases (Betea et al 2004, Horie et al 2010.…”
Section: Molecular Targeted Treatmentmentioning
confidence: 99%